Biocompatible ionic liquids in high-performing organic electrochemical transistors for ion detection and electrophysiological monitoring - Li, Ting (2022)
Organic electrochemical transistors (OECTs) have recently attracted attention due to their high transconductance and low operating voltage, which makes them ideal for a wide range of biosensing applications. Poly-3,4-ethylenedioxythiophene:poly-4-styrenesulfonate (PEDOT:PSS) is a typical material used as the active channel layer in OECTs. Pristine PEDOT:PSS has poor electrical conductivity and additives are typically introduced to improve its conductivity and OECT performance. However, these additives are mostly either toxic or not proved to be biocompatible. Herein, a biocompatible ionic liquid [MTEOA][MeOSO3] is demonstrated to be an effective additive to enhance the performance of PEDOT:PSS based OECTs. The influence of [MTEOA][MeOSO3] on the conductivity, morphology and the redox process of PEDOT:PSS are investigated. The PEDOT:PSS/[MTEOA][MeOSO3] based OECT exhibits high transconductance (22.3 ± 4.5 mS μm-1), high μC* (the product of mobility μ and volumetric capacitance C*) (283.80 ± 29.66 F cm-1 V-1 s-1), fast response time (~40.57 μs) and excellent switching cyclical stability. Next, the integration of sodium (Na+) and potassium (K+) ion-selective membranes with the OECTs is demonstrated, enabling selective ions detection in the physiological range. In addition, flexible OECTs are designed for electrophysiological (ECG) signals acquisition. These OECTs have shown robust performance against physical deformation and successfully recorded high quality ECG signals.